2009
DOI: 10.1371/journal.ppat.1000402
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Dependent Expansion of TNF Receptor II–Positive Regulatory T Cells with Enhanced Suppressive Activity in Adults with Severe Malaria

Abstract: Severe Plasmodium falciparum malaria is a major cause of global mortality, yet the immunological factors underlying progression to severe disease remain unclear. CD4+CD25+ regulatory T cells (Treg cells) are associated with impaired T cell control of Plasmodium spp infection. We investigated the relationship between Treg cells, parasite biomass, and P. falciparum malaria disease severity in adults living in a malaria-endemic region of Indonesia. CD4+CD25+Foxp3+CD127lo Treg cells were significantly elevated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 45 publications
9
132
1
3
Order By: Relevance
“…Likewise, an increase in the number of CD4 + CD25 + Foxp3 + Tregs has been observed in the peripheral blood of humans infected with P. falciparum (7,8) or P. vivax (9), and is apparently associated with P. falciparum parasitemia (10). Similar results were obtained from murine malaria models using P. yoelii or P. berghei (11,12).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Likewise, an increase in the number of CD4 + CD25 + Foxp3 + Tregs has been observed in the peripheral blood of humans infected with P. falciparum (7,8) or P. vivax (9), and is apparently associated with P. falciparum parasitemia (10). Similar results were obtained from murine malaria models using P. yoelii or P. berghei (11,12).…”
supporting
confidence: 73%
“…Phenotypic characterization of Tregs from malaria patients in Western Papua New Guinea demonstrated an upregulation of Foxp3 accompanied by increased suppressive function in patients with severe malaria, but not in those with uncomplicated malaria (8). The results of these studies suggest that CD4 +…”
Section: Discussionmentioning
confidence: 75%
“…Two recent studies in adults have shown that FOXP3 + T regs are expanded in infected versus noninfected adults as well as exposed versus nonexposed adults (73,74). Similar to these recent studies in adults, previous studies with cord blood have examined whether T regs are more likely to be obtained from mothers who have evidence of current or prior malaria.…”
Section: Cd25mentioning
confidence: 89%
“…Recent studies show that T regs can modify susceptibility to disease (77,78) and contribute to whether the host immune responses are protective or pathological in response to infection with P. falciparum parasites (73,(79)(80)(81)(82). The nature of the initial exposure to malaria Ags likely affects the potentially diverse roles assumed by T regs in malaria infection.…”
Section: Cd25mentioning
confidence: 99%
“…The role of distinct Treg subsets in AML is currently not known, however, a functionally active Treg subset should have a high bone marrow migratory capacity (16). TNF receptor-2 (TNFR2) expression has recently been demonstrated to identify highly functional Tregs in healthy donors (17,18) and in various diseases such as malaria (19), diabetes (20), and cancer (21). TNFR2…”
Section: Introductionmentioning
confidence: 99%